THINK-PAIR-SHARE MODEL AS SOLUTION TO DEVELOP STUDENTS’ CRITICAL THINKING IN ISLAMIC STUDIES: IS IT EFFECTIVE? - Mohammad Kurjum; Abdul Muhid; Muhammad Thohir (LPMPP Universitas Negeri Yogyakarta, 2020)
One type of cooperative learning methods is Think Pair Share (TPS). This study aimed at examining the contribution of the TPS method in increasing students' critical thinking in Islamic studies. Particularly, the study investigated the significances of the difference between learned students using TPS method and conventional method, and the effectiveness of TPS learning method. This study used an experimental group and a control group. It is a quasi-experiment with pre-test and post-tests non equivalent control group design. The population of this research are students who take courses in Islamic studies. Samples are taken randomly by taking two classes for an experimental class and a control class. The technique of collecting data was tests, while the technique of data analysis used the statistical technique of t-test (independent and paired samples) within the application of the SPSS release 24 program. The results of the study indicate that there is a significant difference (sig .000) between groups of students who are taught by the TPS Method and conventional Method. In addition, the TPS method has also proven to be effective for teaching Islamic studies which shows a significant difference (sig .000) between the pre-test and post-test.